China’s Economic Development - Brada, Josef C.; Brada, Josef C.; Wachtel, Paul.; Wachtel, Paul.; Yang, Dennis Tao.; Yang, Dennis Tao. (Palgrave Readers in Economics, 2014)
This collection of papers is from Palgrave's journal Comparative Economic Studies, carefully selected by a team of expert editors, this volumes collates the most sophisticated works to provide the readers with an essential guide to the economic development of China.